Predictors of recurrence in early hepatocellular carcinoma patients treated with surgical resection. Issue 1 (15th November 2021) - Cheng, Tzu‐Hsuan; Cheng, Yu‐Ming; Wu, Chao‐Chuan; Tzeng, I‐Shiang; Wang, Chia‐Chi
Abstract: Although surgical resection is a curative treatment for early hepatocellular carcinoma (HCC), the incidence of recurrence is still high. The factors associated with HCC recurrence are unclear and deserve investigation. The early HCC patients receiving surgical resection in Taipei Tzu Chi Hospital were enrolled retrospectively. Those with histologically microvascular invasion and largest tumor size >5 cm were excluded. Aggressive recurrence was defined as multiple recurrence (>3), invasion to vessel or extrahepatic metastasis at the first time of recurrence. A total of 125 HCC patients (86 male; mean age 68.74 ± 11.57 year‐old) were included for final analysis. The survival rate was 96%, 91.2%, and 89.6%, at year 1, 3, and 5, respectively. Sixty one (48.8%) patients had HCC recurrence during the median follow‐up duration of 4.4 years. Of them, aggressive recurrence was present in 17 (27.4%) patients. Among patients with recurrent HCC, those with aggressive recurrence had worse survival rates than those without ( P  = .008). Multifocal tumor was the predictor associated with HCC recurrence using logistic regression analysis; tumor size was associated with earlier recurrence in aggressive recurrence of HCC using stepwise method ( P  = .042). Although early HCC patients had satisfactory 5‐year survival rates after surgical resection, the incidence of HCC recurrence was still high. The presence of aggressive recurrence had a negative impact on overall survival. Multifocal tumor in histology has higher risk of HCC recurrence, but not the pathologic grade of differentiation. Tumor size was associated with early recurrence in HCC patients with aggressive recurrence.